Laser nanocrystallisation and corrosion behaviour of electroless Ni–W–P coating with high phosphorus content. (July 2014) - Liu, H.; Yao, H. L.; Viejo, F.; Harrison, G.; Thompson, G. E.; Liu, Z.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper reports an investigation of microstructural characteristics in electroless Ni–3·9W–13·4P (wt.%) coating by laser nanocrystallisation using a quantitative X–ray diffraction (XRD) method and scanning electron microscopy (SEM) with energy dispersive X–ray spectroscopy (EDX). The corrosion resistance of the coatings before and after laser treatment has been evaluated in 0·5 M H2SO4 solution by potentiodynamic polarisation and electrochemical impedance spectroscopy (EIS) techniques. The results show that the laser treatment improves the corrosion resistance of the coatings. The corrosion mechanism has been studied and correlated to the microstructural characteristics including volume fraction of INi3P/Itotal, microstrain, and the crystallite size of the Ni and Ni3P phases.